Theoretical Investigation of Thiol-Ene Click Reactions: A DFT Perspective - Findik, V.; Degirmenci, Isa; Çatak, Ş.; Aviyente, V. (Elsevier Ltd, 2019)
In this study, a detailed quantum chemical investigation of the contribution of phenyl thiol derivatives in thiol-ene reaction mechanism has been carried out for the first time. DFT calculations have been used to investigate the role of substitution in thiol-ene reactions. It is well known that the reaction mechanism is strongly controlled by the kP/kCT ratio, where kP is the propagation rate constant of the thiyl radical's addition to the alkene and kCT is the rate constant of chain transfer to a thiol. The electrophilic nature of the phenylthio radicals and the singlet-triplet (S-T) gap of alkenes are mainly responsible for the variation of the activation barriers for the propagation reaction, this demonstrates the importance of the ene functionality on the propagation reaction. A correlation between the radical stabilization energy of the carbon centered radical intermediate and the chain transfer activation energy could not be established. The transition structures of the chain transfer reactions were shown to be stabilized by intramolecular interactions, which have lowered the activation barriers. In this study, we underlie the kP/kCT ratio which is highly dependent not only on the alkene functionality, but also on the thiol functionality. Tailor-made polymers can be obtained by altering the substituents or their positions, and the computational procedure described herein is expected to guide the synthesis. © 2018 Elsevier Ltd
Keywords: Chain-Transfer; Click Reaction; DFT; Propagation; Substituent Effect; Thiol-Ene Reaction